A Solution Method for Semidefinite Variational Inequality with Coupled Constraints - Wang, Li; Wang, Shiyun (Communications in Mathematics and Applications, 2013)
The semidefinite variational inequalities with coupled constraints are introduced. The properties of the symmetric matrices value functions that form coupled constraints are discussed. A method involving the augmented Lagrange function is proposed for solving the semidefinite variational inequalities with coupled constraints. The convergence of the method is proved.